Elastoplastic Properties of (Pr, Ce)O2-δ Thin Films. (2nd June 2015) - Swallow, Jessica G.; Kim, Jae Jin; Bishop, Sean R.; Smith, James F.; Tuller, Harry L.; Van Vliet, Krystyn J.
Abstract : Electrode materials exhibiting desired ion transport and reactivity properties for energy conversion devices such as solid oxide fuel cells generally also exhibit significant coupling between electrochemistry and mechanics. Properties and responses of thin films representing active electrode dimensions may differ significantly from bulk counterparts due to increased grain boundary densities, space charge effects, or strain. Here, we quantify elastic and plastic properties for the model SOFC cathode material Pr x Ce1- x O2- δ via nanoindentation. We consider statistical analysis in detail, to quantify uncertainty associated with this method. We confirm no statistically significant difference in Young's elastic modulus E as a function of Pr dopant concentration at room temperature, or in E of films compared to bulk. In contrast, hardness of thin films exceeds that reported for bulk counterparts at room temperature.